Synthesis of robust discrete guidance system for solid body with incomplete state vector measurements - Tунік A.A.; Басанець, О.П. (Proceedings of National Aviation University (archive), 2010)
The paper is deals system synthesis method of the robust control. The method is based on estimation of perfo-?mance and robustness represented by Н2 - and Н - norms accordingly. Particularities of the control object (solid body) establish the following sequence of steps in order to solve a problem: 1) restoring the full state-space vector applying the Luenberger observer; 2) optimal linear-quadratic regulator synthesis; 3) utilization the procedure of Н2/Н robust optimization. This technique has been applied taking into account the constraints on oscillations of the closed-loop system. The same procedure has been applied without the above-mentioned constraints. Simulation results have confirmed the effectiveness and efficiency of the proposed approach.